Seed Dispersal by Ants in Three Early-Flowering Plants - Pavol Prokop; Jana Fančovičová; Zuzana Hlúšková (Insects, 2022)
Interactions between ants and plants vary from being occasionally beneficial to neutral and negative. Ant-mediated dispersal of obligatory myrmecochorous plants is considered mutualistic interaction, providing benefits to plants in terms of seed dispersal. Ants are rewarded by providing elaiosome, sugar, lipid and protein-rich appendages attached to seeds (diaspores). We experimentally examine rates of diaspore removal rates among three species of plants (snowdrop Galanthus nivalis, hollow root Corydalis cava and European wild ginger Asarum europaeum) under field conditions in two study sites in Central Europe. Diaspore morphology is altered by manipulating both elaiosome and seed size. The small-sized acorn ant Temnothorax crassispinus interacts with the snowdrop and hollow root and the moderately-sized red ant Myrmica ruginodis interacts with European wild ginger. Experimental manipulation with elaiosomes yields largely non-significant results. Diaspore removal rates are generally low (snowdrop 10%, hollow root 26%, European wild ginger 34%) probably due to the small size of ants relative to heavy diaspores. Many ants are observed to consume elaiosomes in situ (cheating). We conclude that ant–plant relationships in this case are not mutualistic but rather neutral/slightly negative, because the plants do not obtain any apparent benefits from their interactions with ants.